Handbook of IoT and big data - Solanki, Vijender Kumar 1980-; García Díaz, Vicente; Davim, J. Paulo 1964- (CRC Press, Taylor & Francis Group, 2019)
This multi-contributed handbook focuses on the latest workings of IoT (internet of Things) and Big Data. As the resources are limited, it's the endeavor of the authors to support and bring the information into one resource. The book is divided into 4 sections that covers IoT and technologies, the future of Big Data, algorithms, and case studies showing IoT and Big Data in various fields such as health care, manufacturing and automation. Features Focuses on the latest workings of IoT and Big Data Discusses the emerging role of technologies and the fast-growing market of Big Data Covers the movement toward automation with hardware, software, and sensors, and trying to save on energy resources Offers the latest technology on IoT Presents the future horizons on Big Data
Includes index
Keywords: Internet der Dinge; Big Data; COMPUTERS / Database Management / Data Mining; TECHNOLOGY / Electricity; TECHNOLOGY / Operations Research; Internet of things / Handbooks, manuals, etc; Big data / Handbooks, manuals, etc; Embedded Internet devices / Handbooks, manuals, etc; Electronic books